Application Of Web-Based Archiving Information System (E-Sip) at BPK RI Yogyakarta - Susilawati Desi; Widadi Sigit; Parwoto; Maurine Rr. Sandrina; Polanunu Ummul (E3S Web of Conferences, 2023)
Nowadays, almost every aspect of daily life cannot be separated from digital technology. Modern globalization has accelerated the development of information technology and information systems. Because the user has a specific need, organizations like BPK RI DIY are still resistant to manual document retrieval because they are inefficient and ineffective. This is because the user has a specific need. As such, the goal of developing the web-based application of Aplikasi Sistem Informasi Pengarsipan (E-SIP) is to facilitate archiving issuance. In this application, which was created utilizing the waterfall model, the front-end and back-end frameworks were ReactJS for the front end and NetstJS for the back end, both of which are based on NodeJS for databases using MYSQL. This technique uses the Black box for the GUI of the inactive archive application. Based on test results showing that the archiving application is simple to use and understand, it can be assumed that the application can help organizations like BPK RI DIY in archiving management.